Numerical modelling of different types of nanofluids used to enhance the thermal performance of automotive radiator. (19th June 2023) - Al-Araji, Karaar Mahdi; Almoussawi, M.A.; Hachim, Dhafer M.; Alwaan, Kareem J.
Nanofluids are used to reduce the amount of heat and to increase the thermal performance of the automotive engine. In this work, the effect of nanofluids on the thermal performance of automotive radiators has been studied numerically using the COMSOL Multiphysics software V.5.4 on three types of nanofluids (Al2 O3, CuO and MWCNT) at different volume concentrations of 0.5%, 1, 2% and at different flow rates (4, 6, 8) L/min with inlet temperatures of 60°C, 70°C and 80°C. Results were compared with previous studies with high sobriety to verify the numerical analysis results. The results found an excellent convergence of 6.2% for experimental research and 7.6% for numerical studies. The results also showed that the best thermal performance is obtained by using MWCNT nanofluid. The highest percentage of improvement obtained in the Nusselt number was 25.83%, 42.37%, and 59.7% at volume concentrations of 0.5%, 1%, and 2%, respectively.